Simulation of SAW Filters as Planar Waveguides with N Segments - Jungwirth, Mario; Pöcksteiner, Norbert; Weigel, Robert (Austrian Acoustics Association Fachtagung, 2000)
For the simulation of SAW-filters it can be useful to model the filters as planar waveguides, consisting of several segments with assigned material parameters (phase velocities, stiffness constants). In the case of complex structures (such as transversely coupled resonator filters) a transverse velocity profile consisting of more (N) segments can be determined. For such structures the present work provides the complete analysis based on a scalar potential as the wave-describing quantity. We obtain a complete set of orthonormal modes into which a transverse excitation can be expanded in order to study its propagation. The general mode spectrum consists of a discrete spectrum of bound modes, a continuous spectrum of semi-bound modes and finally a continuous spectrum of radiation modes. As to radiation modes, two solutions per eigenvalue exist, therefore they must be orthogonalized to enable expansion with a scalar product. Furthermore, anisotropy is dealt with by a parabolic approximation of the phase velocities. In general, a very good agreement between theoretical and experimental results has been achieved
elib2cris::1512001600,jungwirth2000
Keywords: SAW Filter; Waveguides